Assessment of knowledge, awareness and attitude concerning premarital screening of hemoglobinopathies among medical students: a cross-sectional study - Somraj, Swapna; Dabade, Kuldeep J.; Suryavanshi, Jaya V.; Dhadave, Meenakshi M. (International Journal Of Community Medicine And Public Health, 2025)
Background: Hemoglobinopathies represent a significant challenge for healthcare systems, particularly in resource-limited settings. Comprehensive prevention strategies, including education, screening programs, and policy support are essential to mitigate the burden of these disorders. Methods: A cross-sectional study was conducted among MBBS students of GIMS, Kalaburagi to evaluate the knowledge, awareness and attitude concerning premarital screening of hemoglobinopathies among medical students. Convenience sampling method was used. Data was collected using a semi-structured questionnaire. Scoring system was used and data was analysed using SPSS version 26. Results: In our study involving 426 MBBS students (226 females, 200 males) with a mean age of 20.85 years, most respondents were phase III students, predominantly from an urban background, and 73.7% identified as Hindu. 81.2% were aware of premarital screening, mainly through academic courses (52.2%). 91.3% recognized premarital screening as a reliable diagnostic tool and 73% acknowledged the role of genetic counselling in prevention. Knowledge was significantly associated with the year of study (p<0.001). 66.9% supported mandatory premarital screening. While 65% wanted to raise awareness about hemoglobinopathies, 97.65% were willing to donate blood, and 55.86% expressed readiness to donate bone marrow. Positive attitudes were more prevalent among females (p<0.001) and those with a family history of genetic diseases (p=0.002). Conclusions: This study highlights critical gaps in knowledge and awareness about premarital screening for hemoglobinopathies among medical students. Addressing these gaps through targeted educational and advocacy efforts can play a pivotal role in reducing the global burden of hemoglobinopathies.